Congenital Deficiency of Conventional Dendritic Cells Promotes the Development of Atopic Dermatitis-Like Inflammation - Nishikawa, Yotaro; Fukaya, Tomohiro; Fukui, Takehito; Uto, Tomofumi; Takagi, Hideaki; Nasu, Junta; Miyanaga, Noriaki; Riethmacher, Dieter; Choijookhuu, Narantsog; Hishikawa, Yoshitaka; Amano, Masahiro; Sato, Katsuaki (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) is a common pruritic inflammatory skin disease characterized by impaired epidermal barrier function and dysregulation of T heper-2 (TH2)-biased immune responses. While the lineage of conventional dendritic cells (cDCs) are implicated to play decisive roles in T-cell immune responses, their requirement for the development of AD remains elusive. Here, we describe the impact of the constitutive loss of cDCs on the progression of AD-like inflammation by using binary transgenic (Tg) mice that constitutively lacked CD11chi cDCs. Unexpectedly, the congenital deficiency of cDCs not only exacerbates the pathogenesis of AD-like inflammation but also elicits immune abnormalities with the increased composition and function of granulocytes and group 2 innate lymphoid cells (ILC2) as well as B cells possibly mediated through the breakdown of the Fms-related tyrosine kinase 3 ligand (Flt3L)-mediated homeostatic feedback loop. Furthermore, the constitutive loss of cDCs accelerates skin colonization of Staphylococcus aureus (S. aureus), that associated with disease flare. Thus, cDCs maintains immune homeostasis to prevent the occurrence of immune abnormalities to maintain the functional skin barrier for mitigating AD flare.